The CHAIN-REDS Semantic Search Engine - Carrubba, Carla; Barbera, Roberto; Inserra, Giuseppina (My University, 2013)
e-Infrastructures, and in particular Data Repositories and Open Access Data Infrastructures, are essential platforms for e-Science and e-Research and are being built since several years both in Europe and the rest of the world to support diverse multi/inter-disciplinary Virtual Research Communities. So far, however, it is difficult for scientists to correlate papers to datasets used to produce them and to discover data and documents in an easy way. In this paper, the CHAINREDS project’s Knowledge Base and its Semantic Search Engine are presented, which attempt to address those drawbacks and contribute to the reproducibility of science.
Keywords: CHAIN-REDS; Cloud Computing; Data Repositories; e-Infrastructures; Grid Computing; Linked Data; Search Engines; Semantic Web